The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2005
DOI: 10.1074/jbc.m508656200
|View full text |Cite
|
Sign up to set email alerts
|

Site-specific Monoubiquitination of IκB Kinase IKKβ Regulates Its Phosphorylation and Persistent Activation

Abstract: Transcription factor NF-B governs the expression of multiple genes involved in cell growth, immunity, and inflammation. Nuclear translocation of NF-B is regulated from the cytoplasm by IB kinase-␤ (IKK␤), which earmarks inhibitors of NF-B for polyubiquination and proteasome-mediated degradation. Activation of IKK␤ is contingent upon signal-induced phosphorylation of its T loop at Ser-177/Ser-181. T loop phosphorylation also renders IKK␤ a substrate for monoubiquitination in cells exposed to chronic activating … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
34
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 32 publications
(83 reference statements)
3
34
0
Order By: Relevance
“…Notably, Mdm2 has been previously shown to lead to mono-and polyubiquitination of substrate proteins (34). Monoubiquitination is suggested to be important for regulating the intracellular trafficking of proteins (35,36) as well as for persistent activity of some signaling kinases (37). Although the exact mechanism is not known, our data indicate that ubiquitination of ␤-arrestin1 is induced upon IGF-1R stimulation and this is important for trafficking as well as the prolonged downstream ERK activation.…”
Section: Discussionmentioning
confidence: 51%
“…Notably, Mdm2 has been previously shown to lead to mono-and polyubiquitination of substrate proteins (34). Monoubiquitination is suggested to be important for regulating the intracellular trafficking of proteins (35,36) as well as for persistent activity of some signaling kinases (37). Although the exact mechanism is not known, our data indicate that ubiquitination of ␤-arrestin1 is induced upon IGF-1R stimulation and this is important for trafficking as well as the prolonged downstream ERK activation.…”
Section: Discussionmentioning
confidence: 51%
“…9). In support of this possibility, the activity of IKK␤, a kinase in the NFB pathways, has been shown to be regulated by monoubiquitination (9). Direct identification of ubiquitination sites by mass spectrometry remains technically challenging, especially for higher eukaryotes where knock-in mutation is not nearly as feasible as in yeast cells.…”
Section: Discussionmentioning
confidence: 99%
“…In this vein, it is interesting that Tax is extensively modified posttranslationally by phosphorylation, ubiquitination, and sumoylation (6,17,23). K63 polyubiquitination of IKK␥ and monoubiquitination of IKK␤ are highly induced by Tax (2). Recent data have also suggested that UBC13/UBE2N, an E2-conjugating enzyme involved in IKK activation, can associate with both Tax and IKK␥ and is critical for their K63 polyubiquitination and Tax-mediated IKK activation (27), a conclusion further sup- ported by a cell-free IKK activation system for Tax elegantly established by Shibata et al (28).…”
Section: Discussionmentioning
confidence: 99%